Sector-based portfolio changes of private equity funds during economic shocks - Moritz Wehking; Tim Alexander Herberger (Journal of Asset Management, 2025)
Private equity investments are highly sensitive to economic shocks due to their assets' high leverage and illiquidity. Allocations to PE have significantly increased over the past decade; research on portfolio selections during economic shocks however remains scarce. We bridge this gap by analyzing sector-level re-allocations during three global economic shocks (the DotCom-bust, the Global Financial Crisis, and COVID-19). We do so by comparing the share of sectoral capital six months before each shock with capital allocations made during the shocks, using a dataset of more than 53,000 buy-side transactions. Specific sectors showed increased transactions from PE investors across all shocks, indicating positive perception from investors in times of uncertainty. Our findings entail: Limited Partners need to critically assess industry-orientated investments of General Partners and challenge over-allocation in perceived "safe harbor" industries, especially when General Partners have no specialization in these industries. When the General Partners are industry-specialized, however, Limited Partners can unlock significant return potential when they agree to an extended investment period. For General Partners with expertise in sagging industries, shocks offer investment opportunities as competition shies away and valuations decrease. Companies in sagging industries seeking external capital should target sources other than PE or accept increased return expectations.
Keywords: G01; G11; G23; 330; Portfolio management; Portfolio selection; Private equity funds